The costs and benefits of digitization of land records via simplified application process - Rahman, Sultan Hafeez; Talukder, Sumaiya Kabir (Copenhagen Consensus Center, 2022)
Bangladeshis are closely connected to the land for their livelihood, social norms and economic activities. Hence, for the development of Bangladesh, land administration and management needs an effective system. In this paper, the cost and benefit of digitization of land records, via a simplified (electronic) application process, have been analyzed. The paper exhibits the economic importance of land records, explains the history of land records, observes the present maintenance and situation of land survey and land transfer records, elaborates the methodology of the study, and describes the case study of digitization of the system of Savar land office. The analysis in the paper shows the breakdown of status quo costs and the cost-benefit analysis of the intervention. It then concludes that Bangladesh is highly dependent on land, hence clean land records are very crucial. Looking ahead, once digitization of land records: accurate cadastral survey records of landholding and public lands, land transaction and registration records, as well as land mutation records, are completed and synchronized, as well as be simultaneously accessible at the three nodal offices, i.e., Land Registration, Assistant Commissioner of Lands, and the Deputy Commissioner of the district along with access of relevant data fields to the public, land ownership, tenurial rights and transactions will be fully secure based on the rule of law. This may need to be supplemented by further legal reform.